Whose 'flow' is it anyway? The demographic correlates of 'flow proneness'. (July 2023) - Isham, Amy; Jackson, Tim
Abstract: Flow states represent a form of optimal experience and contribute to higher levels of psychological well-being and enhanced performance. Research has documented certain personality factors that influence people's likelihood of experiencing flow. However, the association between demographic variables and flow proneness in various activities has been less thoroughly explored and existing findings are often inconsistent across studies. This research sought to explore the demographic correlates of flow proneness across different types of activities. We examined flow proneness' relationship with age, gender, socioeconomic status, and educational attainment. Using a largely representative sample of 4000 adults in the UK, participants completed three different measures of flow proneness and reported the activities where they most often experienced flow. Results demonstrated that, despite trends such as higher levels of education being linked to greater flow proneness, especially in work/study activities, the demographic factors had a minimal role in explaining either flow proneness or the activity sites of flow. Regression models containing all four demographic variables explained up to a maximum of 8 % of variation in flow scores. Promisingly, the study implies that the rewards of flow are not reserved only for certain demographic groups but rather should be available across society.